2016
DOI: 10.1007/s10753-016-0369-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ferulic Acid Against Oxidative Stress and Inflammation in Formaldehyde-Induced Hepatotoxicity

Abstract: This study was designed to elucidate the protective effects of ferulic acid (FA) on formaldehyde-induced hepatotoxicity by measuring some routine biochemical parameters, cytokine levels, and oxidative stress-related parameters in addition to YKL-40 in male Wistar albino rats. Tissue superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) activities, and tissue malondialdehyde (MDA) levels were measured. Also, serum YKL-40, TNF-α, IL-6, IL-1β, IL-8, total protein, albumin, total bilirubin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…YKL40 is highly expressed in chronic liver disease patients with liver fibrosis and cirrhosis (Sarma et al 2012). As reported, the link between YKL-40 and ALD is mediated by ROS (Gerin et al 2016). PAI-1 inhibits fibrin degradation, promotes fibrin deposition on blood vessel walls, and stimulates smooth muscle cell proliferation (Hasenstab et al 2000).…”
Section: Discussionmentioning
confidence: 84%
“…YKL40 is highly expressed in chronic liver disease patients with liver fibrosis and cirrhosis (Sarma et al 2012). As reported, the link between YKL-40 and ALD is mediated by ROS (Gerin et al 2016). PAI-1 inhibits fibrin degradation, promotes fibrin deposition on blood vessel walls, and stimulates smooth muscle cell proliferation (Hasenstab et al 2000).…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, coniferyl alcohol ( 7 ) had a moderated anti-hepatitis B virus (HBV) activity [ 32 ]. Ferulic acid ( 9 ) had an in vivo hepato-protective effect against the CCl 4 - and formaldehyde-induced hepatotoxicity [ 33 ] and also a capacity to inhibit the development of hepatic fibrosis by activation of Hepatic Stellate Cells (HSCs) in the presence of liver damage [ 34 ]. Vomifoliol ( 10 ) showed moderate activity against human hepatocarcinoma Hep3B cells [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ferulic acid is a natural compound with a phenolic group which is found mainly in citrus, rice, coffee, etc. In numerous studies, many roles have been identified for this substance, including anticancer, nephroprotective, hepatoprotective and anti-inflammatory activity (25). Sompong et al demonstrated the inhibitory effect of ferulic acid in glycation and oxidative damage of proteins in 2016 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Gerin et al found that ferulic acid could play an inhibitory role in liver damage due to oxidative stress induced by formaldehyde. Having hydroxyl and phenoxyl groups in its structure, ferulic acid can neutralize free radicals (25). Furthermore, it responds to cellular stress and oxidative damage by increasing the level of antioxidant systems such as SOD, GPx and CAT enzymes and decreasing the expression of cytotoxic enzymes (11).…”
Section: Discussionmentioning
confidence: 99%